EFFECT OF FRICTION SOURCE IN THE HYDRAULIC TRANSIENT IN A PIPELINE SYSTEM USING METHOD OF CHARACTERISTICS - HALEEM, DILSHAD ABDUL JABBAR; MUHSEN, MOHAMMED SADIQ (Journal of Duhok University, 2017)
Numerical modelling is real need to analyze transients, since the system of equations representing the phenomena does not have an analytical solution because of the nonlinear term of friction losses. Consequently, the presents study applies the method of characteristics to determine the pressure change variation along a simple pipeline system resulted from hydraulic transient, along with using two different approaches in approximating of the friction term. The performance of numerical scheme is verified, considered against many scenarios and different parameters in the simple pipeline system.  It was found that the two models gives slightly different results in terms of simulating the velocity and the pressure wave velocity in the undertaken scenario of pipe filled system. But follow the same scheme. Also it was approved that the first approach is linear while the second one is not. The effect of wave speed was proven to be a significant influence on the transient state. The study also shows that Flow velocity and pipe frictional coefficient also affects on pressure head proportionally. The computational time interval which gives stable results was proven to be chosen according to Courant stability condition. A MATLAB code has been written and then used in the simulation of test cases.